The agony of labor law: a history from its origins to its confines - Fonseca Alfonso, Yair Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
On the occasion of centenary of the International Labour Organization (ILO), the main objectives of this article are to carry out a historical analysis of labour law and to make a critique of the current labour law. Starting from their origins, its development in the middle ages, its evolution in the modern age, the main advances achieved as a result of the social mobilizations of the nineteenth century and the consolidation of these advances through the twentieth century. Based on the foregoing and through a qualitative methodology, it is manifested as the main research hypothesis to highlight the agony of labor law caused by flexible processes, delabouring through the proliferation of contracts Of service delivery, labor informality and virtualization generated as a result of the great technological advances developed at the end of the twentieth century and consolidated during the run of the 21ST century. Finally, the main findings and results of this research are highlighted: the demonstration of the high informality rates, the impoverishment and affecting the working conditions in Colombia since the decade of the years 90, as well as the need to abide by the provisions of the World Commission on the Future of labor of the ILO, focused on increasing investment in people´s capacities, investing in labor institutions and increasing strategies to promote decent and sustainable work.